2012
DOI: 10.1634/theoncologist.2012-0024
|View full text |Cite
|
Sign up to set email alerts
|

The Risk for Anemia with Targeted Therapies for Solid Tumors

Abstract: Background. Anemia is a common manifestation in patients with cancer. Little is known about the frequency of and risk for anemia with targeted therapies used to treat solid tumors.Methods. We performed a meta-analysis of randomized controlled trials of solid tumors by comparing targeted therapy (alone or in combination) with standard therapy alone to calculate the incidence and relative risk (RR) for anemia events associated with these agents. Overall, 24,310 patients were included in the analysis.Results. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 87 publications
(37 reference statements)
1
30
0
8
Order By: Relevance
“…This may result, in part, due to hyperproliferation of bone marrow blast cells which “crowd out” the non‐malignant cell population thus preventing normal erythroid blast‐forming units and islands from interacting with stem cell factor and bone marrow stromal cells which are thought to be necessary to maintain their differentiation, growth, and division . Additionally, mutations in or therapy‐related inhibition of the intracellular domain of c‐kit (CD117) may also be partly responsible for reduced erythropoiesis by reducing c‐kit‐dependent phosphorylation and the intracellular interaction between c‐kit and the tyrosine kinase domain of the erythropoietin receptor .…”
Section: What Is Cancer‐related Anemia?mentioning
confidence: 99%
See 1 more Smart Citation
“…This may result, in part, due to hyperproliferation of bone marrow blast cells which “crowd out” the non‐malignant cell population thus preventing normal erythroid blast‐forming units and islands from interacting with stem cell factor and bone marrow stromal cells which are thought to be necessary to maintain their differentiation, growth, and division . Additionally, mutations in or therapy‐related inhibition of the intracellular domain of c‐kit (CD117) may also be partly responsible for reduced erythropoiesis by reducing c‐kit‐dependent phosphorylation and the intracellular interaction between c‐kit and the tyrosine kinase domain of the erythropoietin receptor .…”
Section: What Is Cancer‐related Anemia?mentioning
confidence: 99%
“…We currently consider ESA therapy for patients receiving palliative, myelosuppressive chemotherapy with a Hb <10 g/dL and without absolute iron deficiency . It is important to note that although newer targeted therapies such as sunitinib, erlotinib, or trastuzumab commonly contribute to anemia, the ESA package labels do not mention whether these are included under the definition of myelosuppressive agents . When dosing ESA therapy, we prefer subcutaneous (SQ) over the IV route, because doses given IV are cleared from the plasma more quickly and are therefore less effective .…”
Section: Rbc Transfusion Versus Esasmentioning
confidence: 99%
“…The association between anemia and targeted therapy is noteworthy. A previous meta‐analysis demonstrated that there was most likely an association between targeted agents and the type of cancer . Unfortunately, their study did not probe into the association between vandetanib and anemia.…”
Section: Discussionmentioning
confidence: 96%
“…A previous meta-analysis demonstrated that there was most likely an association between targeted agents and the type of cancer. 48 Unfortunately, their study did not probe into the association between vandetanib and anemia. This finding needs to be further investigated in the future.…”
Section: Combined Inhibition Therapy Versus Placebomentioning
confidence: 99%
“…Appropriate and adequate blood flow and oxygen delivery is paramount to free flap viability and success. While these procedures rarely involve significant blood loss, many patients present with pre‐existing anemia related to their cancer or its treatment and may develop a state of postoperative anemia following surgery . Anemia has long been discussed both as a potential advantage to the free flap, but as a complicating issue to the patient.…”
mentioning
confidence: 99%